Cognitive phenotypes in temporal lobe epilepsy utilizing data‐ and clinically driven approaches: Moving toward a new taxonomy. (4th May 2020) - Reyes, Anny; Kaestner, Erik; Ferguson, Lisa; Jones, Jana E.; Seidenberg, Michael; Barr, William B.; Busch, Robyn M.; Hermann, Bruce P.; McDonald, Carrie R.
Abstract: Objective: To identify cognitive phenotypes in temporal lobe epilepsy (TLE) and test their reproducibility in a large, multi‐site cohort of patients using both data‐driven and clinically driven approaches. Method: Four‐hundred seven patients with TLE who underwent a comprehensive neuropsychological evaluation at one of four epilepsy centers were included. Scores on tests of verbal memory, naming, fluency, executive function, and psychomotor speed were converted into z ‐scores based on 151 healthy controls (HCs). For the data‐driven method, cluster analysis ( k ‐means) was used to determine the optimal number of clusters. For the clinically driven method, impairment was defined as >1.5 standard deviations below the mean of the HC, and patients were classified into groups based on the pattern of impairment. Results: Cluster analysis revealed a three‐cluster solution characterized by (a) generalized impairment (29%), (b) language and memory impairment (28%), and (c) no impairment (43%). Based on the clinical criteria, the same broad categories were identified, but with a different distribution: (a) generalized impairment (37%), (b) language and memory impairment (30%), and (c) no impairment (33%). There was a 82.6% concordance rate with good agreement ( κ = .716) between the methods. Forty‐eight patients classified as having a normal profile based on cluster analysis were classified as having generalized impairment (n = 16) or an isolated language/memory impairment (n = 32) based on the clinical criteria. Patients with generalized impairment had a longer disease duration and patients with no impairment had more years of education. However, patients demonstrating the classic TLE profile (ie, language and memory impairment) were not more likely to have an earlier age at onset or mesial temporal sclerosis. Significance: We validate previous findings from single‐site studies that have identified three unique cognitive phenotypes in TLE and offer a means of translating the patterns into a clinical diagnostic criteria, representing a novel taxonomy of neuropsychological status in TLE.